Annual editions - Buskist, William
Annual Editions is a series of over 65 volumes, each designed to provide convenient, inexpensive access to a wide range of current articles from some of the most respected magazines, newspapers, and journals published today. Annual Editions are updated on a regular basis through a continuous monitoring of over 300 periodical sources. The articles selected are authored by prominent scholars, researchers, and commentators writing for a general audience. The Annual Editions volumes have a number of common organizational features designed to make them particularly useful in the classroom: a general introduction; an annotated table of contents; a topic guide; an annotated listing of selected World Wide Web sites; and a brief overview for each section. Each volume also offers an online Instructor's Resource Guide with testing materials. Using Annual Editions in the Classroom is offered as a practical guide for instructors and is available in print or online. Visit www.mhcls.com for more details